Nilai-Nilai Amanah dalam Al-Qur’an: Suatu Kajian dengan Pendekatan Tafsir Maudhu’iy - Fatimah, Fatimah (Al-Riwayah : Jurnal Kependidikan, 2019)
Since a baby born, all kinds of human being are supposed to carry trust bestowed upon every single of them. The values of trust are revealed from the Quran conceptualized within two key points of trust as in Al-risalat and Al-Amanat. This study discusses the definition of trust as the terminology from various perspectives. The word of is defined lexically as calm and not afraid. However, the other translation openly expresses as loyalty, sincerity, trust (tsiqah) or honesty. Nevertheless, in broader understanding, the terminology refers to the righful person who remains morally responsible for their life narration. The method used inthis interpretation approach is maudhu'iy (thematic) as the focus of the study in this discussion. Based on the previous background, the formulation of the main problem being studied is, how trust is reviewed in the Qur'an through the maudhu'iy interpretation approach. The limitations of the problems examined in this discussion are about the trust understanding, the editorial of related verses, the concepts of trust according to the Qur'an. Values of trust in Quran are conclusively established as: (1) human responsibility to God, (2) human responsibility to each other, and (3) human responsibility to himself. Some of the verses from Qur'an are taken into account as the reference. It is clear that the importance of trust associated with the matter of urgency in human life, the religious appeal, the broader scope in life.